Spherical Functions of Fundamental K-Types Associated with the n-Dimensional Sphere - Tirao, Juan Alfredo (2014)
In this paper, we describe the irreducible spherical functions of fundamentalK-types associated with the pair (G, K) = (SO(n + 1), SO(n)) in terms of matrix hypergeometric functions. The output of this description is that the irreducible spherical functions of the same K-fundamental type are encoded in new examples of classical sequences of matrix-valued orthogonal polynomials, of size 2 and 3, with respect to a matrix-weight W supported on [0, 1]. Moreover, we show that W has a second order symmetric hypergeometric operator D.